Analisis Pelaksanaan Projek Penguatan Profil Pelajar Pancasila (P5) Tema Kewirausahaan di SDN 1 Rejotengah Lamongan - Fahmi, Ahmad Hadiqul; Fadlillah, M. (Yayasan Arrahman Nahdlatul Wathan, 2024)
Strengthening the Pancasila Student Profile (P5) with the theme of entrepreneurship at SDN 1 Rejotengah, Lamongan. This research uses a qualitative descriptive approach to describe the project implementation process, collaboration, challenges, and factors that support its success. The results of the research show that 1) The implementation of the Project for Strengthening the Pancasila Student Profile (P5) with the theme of entrepreneurship at SDN 1 Rejotengah was carried out by making products from recycled materials, such as ice cream sticks, banana stem collages, and piggy banks from plastic bottles. This project involves the active role of teachers, principals and students in every stage of activities, from planning to implementation. 2) Obstacles to Implementing the Project for Strengthening the Profile of Pancasila Students (P5) The entrepreneurship theme has several obstacles, namely lack of students' understanding of the concept of recycling and cleanliness of the school environment, limited implementation time due to the involvement of P5 teachers in the Teacher Professional Education Program (PPG), limited facilities and lack of P5 activity equipment and students playing alone when implementing P5. It is hoped that this research can become a reference for other schools in implementing P5 programs with an entrepreneurship theme. Apart from providing entrepreneurial experience to students, this program also instills Pancasila values, such as creativity, responsibility and cooperation, through a project-based learning approach.